2020
DOI: 10.1088/1361-648x/abae18
|View full text |Cite
|
Sign up to set email alerts
|

High-T c Cooper-pair injection in a semiconductor–superconductor structure

Abstract: We observe Andreev reflection in a YBCO-GaN junction through differential conductance spectroscopy. A strong characteristic zero-bias peak was observed and persisted up to the critical temperature of the superconductor with a smaller superconducting order parameter Δ ∼ 1 meV. The presence of Andreev reflection with the small Δ in comparison to its value for high-T c superconductors forms an important milestone toward demonstration of superconducting proximity in high-T c /semiconductor junctions. Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…)]/2 also approaches to zero near the magnetic criticality [30], the edge s odd wave gap will not affect the LDOS at zero-energy. This result is consistent with the ubiquitous presence of zerobias conductance peak in the tunneling spectroscopy of cuprates [10,11,65,66] Here, we elucidate the emergence of nontrivial edge supercurrent in the d + s odd wave state. In the present cluster model with the d + s odd wave gap, the charge current along the x-axis from layer y (Fig.…”
supporting
confidence: 84%
“…)]/2 also approaches to zero near the magnetic criticality [30], the edge s odd wave gap will not affect the LDOS at zero-energy. This result is consistent with the ubiquitous presence of zerobias conductance peak in the tunneling spectroscopy of cuprates [10,11,65,66] Here, we elucidate the emergence of nontrivial edge supercurrent in the d + s odd wave state. In the present cluster model with the d + s odd wave gap, the charge current along the x-axis from layer y (Fig.…”
supporting
confidence: 84%
“…This was illustrated when a cooper-pair was injected into the BFO films. The phenomenon of a superconducting cooper-pair entering a superconductor-semiconductor structure has been reported previously [ 34 , 35 ]. However, more studies are required to understand the relation between the PTCR and the superconductivity of YBCO.…”
Section: Resultsmentioning
confidence: 96%
“…The conductance spectra of cuprate superconductors observed in experiments so far are peak-structure at the zero energy 8,9,[11][12][13][14][15] even though several experiments reported the splitting of the ZBCP 10,37,38 . Our theoretical study, where the p-wave surface attractive interaction is phenomenologically taken into account, demonstrated that the p-wave subdominant pair potential does not split the zero-bias peak.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the subdominant s-wave component splits the zero-energy peak in the local density of states (LDOS) [33][34][35] and gives rise to a spontaneous surface current with breaking the time reversal symmetry (TRS) 36 . In experiments, however, such peak splitting nor TRS breaking has not been observed 8,9,[11][12][13][14][15][16] except for several cases 10,37,38 . More seriously, the induced s-wave pair potential requires an on-site attractive interaction in contradiction to the strong repulsive interaction in the cuprate.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation